Evaluation of load balancing algorithms on overlappiing wireless accesspoints - Marion Olubunmi Adebiyi; Egbe Egbe Adeka; Florence A. Oladeji; Roseline Oluwaseun Ogundokun; Micheal Olaolu Arowolo; Ayodele Ariyo Adebiyi (Institute of Advanced Engineering and Science, 2021)
Wireless networks came into the computing world replacing the costlier and more complex wired method of connecting numerous equipment in the same or different location via the use of cables. It provides the user devices a connection to one another and the greater internet via connections to access points. Generally, 802.11 access point products follow a default strongest signal first approach in selecting user devices or nodes to connect to the access point or overlapping access points. This standard does not make provisions for even distribution of load and hence the quality of service and the throughput in areas of congestion would be reduced. This article brings forward two algorithms used in load balancing and they include round-robin technique and the weighted round-robin technique to be used in the simulation of the distribution of the load amongst the access points with the results collated and compared to clearly show which algorithm is best suited to be used as a standard for access point load distribution.